Production performance of white shrimp Litopenaeus vannamei with super-intensive culture on different rearing densities - Rakhmanda, Andhika; Pribadi, Agung; Parjiyo, Parjiyo; Wibisono, Bobby Indra Gunawan (Jurnal Akuakultur Indonesia, 2021)
This research aimed to evaluate the production performance of white shrimp Litopenaeus vannamei with super-intensive culture on different rearing densities. The research was conducted at PT. Dewi Laut Aquaculture, Cikelet, Garut, West Java. As many of 8 ponds were used and divided into 2 groups based on the stock density of shrimp, 550 ind/m2 and 650 ind/m2, and reared for 99 days. The results showed that super-intensive shrimp culture at the density of 550–650 ind/m2 potentially produced shrimp with average body weight ranged from 15.91–19.31 g, survival rate 62.67–87.95%, growth 0.16 to 0.20 g/day, FCR 1.35–1.66, and productivity reach 5.55–9.19 kg/m2. There were no significant differences between the two stocking densities in body weight, growth, and feed conversion performance, while ponds with higher rearing density had better survival and productivity than ponds with lower rearing density. L. vannamei cultured at a density of 650 ind/m2 produces the best performance and most feasible to be applied in super-intensive white shrimp cultivation. Keywords: Litopenaeus vannamei, super-intensive, high-density, production performance ABSTRAK Penelitian ini bertujuan untuk mengevaluasi kinerja produksi udang vaname pada sistem super- intensif dengan padat penebaran berbeda. Penelitian dilaksanakan di tambak PT. Dewi Laut Aquaculture, Cikelet, Garut, Jawa Barat, menggunakan 8 petak tambak. Tambak dibagi menjadi 2 kelompok, masing-masing 4 petak tambak dengan padat tebar udang 550 ekor/m2 dan 4 petak tambak lainnya dengan padat tebar 650 ekor/m2 dengan masa pemeliharaan 99 hari. Hasil penelitian menunjukkan bahwa budidaya udang vaname pada sistem super-intensif dengan padat tebar 550–650 ekor/m2 dapat menghasilkan udang dengan bobot rata-rata berkisar antara 15.91–19.31 g, sintasan 62.67–87.95%, pertumbuhan 0.16–0.20 g/hari, konversi pakan (FCR) 1.35–1.66, dan produktivitas mencapai 5.55–9.19 kg/m2. Tidak ada perbedaan nyata antara kedua padat penebaran pada kinerja bobot, pertumbuhan harian, dan FCR; sementara tambak dengan kepadatan tinggi memiliki nilai sintasan dan produktivitas yang lebih tinggi dari tambak dengan kepadatan rendah. Padat penebaran 650 ekor/m2 menghasilkan kinerja produksi terbaik dan paling layak untuk diaplikasikan dalam budidaya udang vaname super-intensif. Kata kunci : Litopenaeus vannamei, padat tebar tinggi, super-intensif, kinerja produksi